Aspect sensitivity measurements of polar mesosphere summer echoes using coherent radar imaging - Chilson, P. B.; Yu, T.-Y.; Palmer, R. D.; Kirkwood, S. (CCSD, 2002)
International audience The Esrange VHF radar (ESRAD), located in northern Sweden (67.88° N, 21.10° E), has been used to investigate polar mesosphere summer echoes (PMSE). During July and August of 1998, coherent radar imaging (CRI) was used to study the dynamic evolution of PMSE with high temporal and spatial resolution. A CRI analysis provides an estimate of the angular brightness distribution within the radar's probing volume. The brightness distribution is directly related to the radar reflectivity. Consequently, these data are used to investigate the aspect sensitivity of PMSE. In addition to the CRI analysis, the full correlation analysis (FCA) is used to derive estimates of the prevailing three-dimensional wind associated with the observed PMSE. It is shown that regions within the PMSE with enhanced aspect sensitivity have a correspondingly high signal-to-noise ratio (SNR). Although this relationship has been investigated in the past, the present study allows for an estimation of the aspect sensitivity independent of the assumed scattering models and avoids the complications of comparing echo strengths from vertical and off-vertical beams over large horizontal separations, as in the Doppler Beam Swinging (DBS) method. Regions of enhanced aspect sensitivity were additionally shown to correlate with the wave-perturbation induced downward motions of air parcels embedded in the PMSE.